International human resource management - Briscoe, Dennis R. 1945- (Prentice Hall, 1995)
This up-to-date, comprehensive reference was written in response to the expanding role of international content within Human Resource Management. Reflecting both empirical research and the state of practice in the industry, it reflects information from consulting firms, national and global HRM conferences, and interviews with HRM managers in multinational and global firms. To reinforce concepts and principles, author Dennis R. Briscoe incorporates IHRM in Action boxes featuring actual companies. In addition, an entire chapter (9) explores the future of IHRM, complete with the latest references and research.
Keywords: Entreprises multinationales - Etats-Unis - Personnel - Direction; Entreprises multinationales - Personnel - Direction; Entreprises multinationales - États-Unis - Personnel - Direction; Internationale ondernemingen; Personeelsmanagement; Multinationales Unternehmen; International business enterprises -- Personnel management; International business enterprises -- United States -- Personnel management; Humanvermögen; Personalpolitik; Personalentwicklung; USA